Rhetorical questions or rhetorical uses of questions? - Špago Džemal (ExELL (Explorations in English Language and Linguistics))
This paper aims to explore whether some rhetorical questions contain certain linguistic elements or forms which would differentiate them from answer-eliciting and action-eliciting questions, and thereby hint at their rhetorical nature even outside the context. Namely, despite the fact that the same questions can be rhetorical in one context, and answer-eliciting in another, some of them are more likely to be associated with rhetorical or non-rhetorical use. The analysis is based on extensive data (over 1200 examples of rhetorical questions taken from 30 plays by two British and two American writers), and the results are expected to give an insight into whether we can talk about rhetorical questions or just a rhetorical use of questions.